Interspecies RNA Interactome of Pathogen and Host in a Heritable Defensive Strategy - Legüe, Marcela; Aguila, Blanca; Calixto, Andrea (Frontiers in Microbiology, 2021)
Communication with bacteria deeply impacts the life history traits of their hosts. Through specific molecules and metabolites, bacteria can promote short and long term phenotypic and behavioral changes in the nematode Caenorhabditis elegans. The chronic exposure of C. elegans to pathogens promotes the adaptive behavior in the host's progeny called Pathogen Induced Diapause Formation (PIDF). PIDF is a pathogen avoidance strategy induced in the second generation of animals infected and can be recalled transgenerationally. This behavior requires the RNA interference machinery and specific nematode and bacteria small RNAs (sRNAs). In this work, we assume that RNAs from both species co-exist and can interact with each other. Under this principle, we explore the potential interspecies RNA interactions during PIDF triggering conditions, using transcriptomic data from the holobiont. We study two transcriptomics datasets: the dual sRNA expression of Pseudomonas aeruginosa PAO1 and C. elegans in a transgenerational paradigm for six generations. Second, the simultaneous expression of sRNAs and mRNA in intergenerational PIDF. We focus on those bacterial sRNAs that are systematically overexpressed in the intestines of animals compared with sRNAs expressed in host-naïve bacteria. We selected diverse in silico methods that represent putative mechanisms of RNA-mediated interspecies interaction. These interactions are: heterologous perfect and incomplete pairing between bacterial RNA and host mRNA; sRNAs of similar sequence expressed in both species that could mimic each other; and known or predicted eukaryotic motifs present in bacterial transcripts. We conclude that a broad spectrum of tools can be applied for the identification of potential sRNA and mRNA targets of the interspecies RNA interaction that can be subsequently tested experimentally.